Evaluation of the safety, tolerability, and efficacy of pimavanserin versus placebo in patients with Alzheimer's disease psychosis: a phase 2, randomised, placebo-controlled, double-blind study. Issue 3 (March 2018) - Ballard, Clive; Banister, Carol; Khan, Zunera; Cummings, Jeffrey; Demos, George; Coate, Bruce; Youakim, James M; Owen, Randall; Stankovic, Srdjan; ,
Summary: Background: Pimavanserin is a selective 5-HT2A receptor inverse agonist and antagonist approved in the USA for the treatment of hallucinations and delusions associated with Parkinson's disease psychosis. No safe or effective pharmacological treatment is approved for psychosis in patients with Alzheimer's disease. Therefore, we aimed to evaluate the safety, tolerability, and efficacy of pimavanserin versus placebo in patients with Alzheimer's disease psychosis. Methods: We did a phase 2, randomised, double-blind, placebo-controlled, single-centre (with multiple affiliated nursing home sites across the UK) study. We included participants of either sex who were aged 50 years or older with possible or probable Alzheimer's disease and psychotic symptoms including visual or auditory hallucinations, delusions, or both. Participants were randomly assigned (1:1) to 12 weeks of oral treatment with either pimavanserin (two 17 mg tablets daily) or placebo, with use of permuted block sizes of four and stratified by baseline Mini-Mental State Examination (MMSE) total score (<6 or ≥6) and Neuropsychiatric Inventory–Nursing Home version (NPI–NH) psychosis score (<12 or ≥12). Participants, caregivers, the study sponsor, and study personnel at the clinic site were masked to treatment assignment. The primary endpoint was mean change from baseline to week 6 in the NPI–NH psychosis score for pimavanserin versus placebo in the modified intention-to-treat population. Sustained benefit and safety of pimavanserin were assessed through week 12. This study is registered atClinicalTrials.gov, numberNCT02035553 . Findings: Between Jan 16, 2014, and Oct 27, 2016, 345 participants across 133 nursing homes were screened, of whom 181 were randomly assigned treatment (n=90 pimavanserin and n=91 placebo). 178 participants were included in the modified intention-to-treat population. Mean total baseline NPI–NH psychosis scores were 9·5 (SD 4·8) for the pimavanserin group and 10·0 (5·6) for the placebo group. Mean change in the NPI–NH psychosis score at week 6 was −3·76 points (SE 0·65) for pimavanserin and −1·93 points (0·63) for placebo (mean difference −1·84 [95% CI −3·64 to −0·04], Cohen's d =−0·32; p=0·045). By week 12, no significant advantage for pimavanserin versus placebo was observed for the overall study population (treatment difference −0·51 [95% CI −2·23 to 1·21]; p=0·561). Common adverse events were falls (21 [23%] of 90 participants in the pimavanserin group vs 21 [23%] of 91 in the placebo group), urinary tract infections (20 [22%] vs 25 [28%]), and agitation (19 [21%] vs 13 [14%]). Eight (9%) participants on pimavanserin and 11 (12%) on placebo discontinued treatment because of adverse events. No detrimental effect was observed on cognition or motor function in either group. Interpretation: Pimavanserin showed efficacy in patients with Alzheimer's disease psychosis at the primary endpoint (week 6) with an acceptable tolerability profile and without negative effect on cognition. Further follow-up to week 12 did not show significant advantage for pimavanserin versus placebo. Funding: ACADIA Pharmaceuticals.